Unveiling Barriers to Recycling with a Focus on Design: An Ishikawa Diagram-Based Approach with Industrial Application - Rohde, Katharina; Gonzalez, Barbara Fernandez; Budde, Finn Lukas; Ott, Manuel; Mozgova, Iryna; Mendibe, Alain Alonso (Safe and Sustainable Value Creation by Design - Proceedings of the 21st Global Conference on Sustainable Manufacturing)
The circular economy offers decisive advantages over the currently prevalent linear economy in industry. Firstly, the reuse of products, individual parts and material reduces the need for new production or generation and the associated consumption of energy and resources. Secondly, it helps to avoid the generation of waste. Early consideration of circular economic principles in product development processes is essential to specifically promote reuse, reparability and recycling. Efficient recycling of assemblies requires well-defined strategies. However, various challenges hinder the efficiency of technical recycling processes in industrial applications. This paper presents an Ishikawa (fishbone) diagram-based approach to systematically identify and categorize these influences. The method is implemented within an industrial framework, highlighting key obstacles such as material composition, design constraints, use of technology, framework conditions, economic limitations and regulatory challenges. By applying a scenario analysis, this approach examines potential future developments and their impact on recycling-oriented design choices. This helps to identify critical influencing factors and supports the development of resilient and sustainable industrial practices. This framework will serve as the foundation for developing an automated approach to circular design, enabling industries to more effectively integrate sustainability into their processes and adapt to changing environmental demands.

Digital product passports and the challenge of product structure granularity: A decision-making framework for the level of DPP integration - Rohde, Katharina; Budde, Finn Lukas; Patrício, Bárbara; Ferreira, Tânia; Gonçalves, Ana; Ott, Manuel; Mozgova, Iryna (Proceedings of the Design Society)
Political goals, emerging EU sustainability regulations, and industrial digitalization are driving the introduction of Digital Product Passports (DPPs) to enhance transparency, traceability, and compliance across product life cycles. However, the appropriate granularity of DPP integration across product architectures remains ambiguous. This paper introduces a structured, decision-oriented framework that links product structure, regulatory relevance, and information depth to define consistent DPP levels, supporting both industry implementation and future standardization.
Keywords: digital product passport; product architecture; circular economy; information granularity; decision-making framework

Optimierung modularer Produkte für die Mobilität: Ein Klassifizierungsrahmen für zirkuläre Produkte - Rohde, Katharina; Ott, Manuel; Budde, Finn Lukas; Mozgova, Iryna (Solving Conflicts on the Way to Sustainable Mobility: Technische und betriebswirtschaftliche Aspekte)
Für die Aufrechterhaltung der natürlichen Ressourcen ist eine effiziente Nutzung dieser essenziell. Vor diesem Hintergrund untersucht das vorliegende Paper die Rolle der Kreislaufwirtschaft als wegweisendes Wirtschaftsmodell, das von der Europäischen Union gefördert wird. Ziel der Kreislaufwirtschaft ist es, den Ressourcenverbrauch und die Abfallproduktion zu minimieren, indem ein kontinuierlicher Kreislauf aus Nutzung, Wiederverwendung und Recycling von Materialien geschaffen wird. Ein zentraler Aspekt dabei ist der Produktentwicklungsprozess (PEP) - ein vielschichtiger Prozess mit zahlreichen Einflussfaktoren und theoretisch unbegrenzten Gestaltungsmöglichkeiten. Diese Vielfalt führt jedoch zu erheblichen Entscheidungsunsicherheiten, die die Umsetzung von Kreislaufwirtschaftsprinzipien erschweren können. Um diese Herausforderungen zu adressieren, wird ein methodischer Prozess vorgestellt, der eine systematische Klassifizierung im Zusammenhang mit umliegenden Bauteilen ermöglicht. Die Methodik basiert auf einer strukturierten Bewertung von Bauteilen hinsichtlich ihrer Relevanz für die Kreislaufwirtschaft. Dabei werden zentrale Aspekte wie Wiederverwendbarkeit, Recyclingfähigkeit und Ressourceneffizienz berücksichtigt, darunter: • Handelt es sich um ein Gebrauchs- oder Verbrauchsprodukt? • Ist das Bauteil eine Wiederverwendung oder eine Neufertigung? • Ist das Bauteil standardisiert, zugekauft oder individuell ausgerichtet? • Welche primäre Funktion nimmt das Bauteil ein? Diese strukturierte Klassifizierung unterstützt die Entscheidungsfindung bereits früh im PEP. Sie ermöglicht es Produktentwickelnden, Potenziale für die Kreislaufwirtschaft frühzeitig zu erkennen und gezielt nachhaltige Maßnahmen zu ergreifen. Die entwickelte Methodik bildet somit eine Grundlage für die Integration kreislaufwirtschaftlicher Prinzipien in den Entwicklungsprozess. Insbesondere im Kontext moderner Anforderungen des Mobility Management zeigt sich ihr Potenzial, nachhaltige Innovationen gezielt zu fördern und die Umsetzung der Kreislaufwirtschaft in der industriellen Praxis zu erleichtern.